A bioactive magnesium phosphate cement incorporating chondroitin sulfate for bone regeneration. (16th April 2021) - Shi, Yubo; Yu, Ling; Gong, Changtian; Li, Wei; Zhao, Yingchun; Guo, Weichun
Abstract: Magnesium phosphate cement (MPC) has been evaluated as an inorganic bone filler due to its favorable biocompatibility, biodegradability, rapid setting, high initial strength, and osteogenic potential. However, the setting time of MPC is so rapid that it makes it difficult to use in practice, and the clinical properties of MPC could be further be improved by adding bioactive materials. Here we developed novel bioactive chondroitin sulfate (CS)-MPC composites (CS-MPCs) by incorporating different amounts of CS into MPC. The compositions, microstructures, and physiochemical properties of CS-MPCs and their induced in vitro cellular responses and in vivo bone regeneration properties were evaluated. CS-MPCs had a longer setting time, lower hydration temperature, higher compressive strength, and more neural pH than MPC. CS-MPCs demonstrated similar degradation ratios relative to MPC in Tris-HCl solution. CS-MPCs promoted pre-osteoblast cell proliferation, attachment, and differentiation in vitro and enhanced bone formation surrounding implants in vivo . In conclusion, through CS modification, our novel CS-MPCs have improved physiochemical properties that enhance compatibility in vitro and bone regeneration in vivo, making them attractive materials for bone regeneration.